The Role of Project-Based Learning in Boosting Student Communication Confidence - Purnami, Ida Ayu Oka; Widiadnya, I Gusti Ngurah Bagus Yoga (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Effective communication is an important skill that students must possess, but often students struggle to speak confidently. One of the approaches that has been proven to improve communication skills is Project-Based Learning (PBL). This research aims to analyze the influence of Project-Based Learning (PBL) on improving students' communication skills, particularly in terms of confidence and collaboration skills. The research method used is a Systematic Literature Review (SLR), which collects data from 15 reputable journal articles relevant to this topic. Data were analyzed using qualitative analysis techniques to evaluate the findings related to the impact of PBL on student communication. The research results show that PBL significantly enhances students' confidence in speaking, interpersonal communication skills, and teamwork collaboration. In addition, the effective implementation of PBL requires good project design, technological support, and the active role of educators in facilitating learning. This study concludes that PBL is an effective approach to enhancing students' communication skills. The implication is that educators need to design relevant communication-based projects and provide adequate support to achieve optimal results.The implication is that educators need to design relevant communication-based projects and provide adequate support to achieve optimal results.